2017
DOI: 10.1248/bpb.b16-00770
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Cationic Liposomes with Cholesteryl-PEG Prevents Their Aggregation in Human Urine and Enhances Cellular Uptake by Bladder Cancer Cells

Abstract: Intravesical drug delivery by cationic liposomes (Cat-LPs) represents a potent nanotechnology for enhancing therapeutic effects against bladder disorders. However, preventing the aggregation of Cat-LPs in urine poses a significant barrier. We report on an examination of the effect of modifying liposomes with polyethylene glycol (PEG) lipids to prevent Cat-LPs from aggregating in human urine. Although Cat-LPs underwent significant aggregation in human urine, introducing 5 mol% of PEG2k lipid or 2 mol% of PEG5k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…For example, the changes of the tonicity of the nasal environment may considerably affect the liposomal formulation stability and the drug-releasing rate [51]. Formulations that can minimize the particle aggregation at nasal pH would be required to ensure the intranasal stability of liposomes, as cationic liposomes are prone to aggregation in physiological conditions [88]. Setting reliable in vitro or ex vivo study models that can test the impact of these formulation factors would be essential for facilitating the development of liposome formulations for nose-to-brain delivery.…”
Section: Conclusion: Implications For Future Developmentmentioning
confidence: 99%
“…For example, the changes of the tonicity of the nasal environment may considerably affect the liposomal formulation stability and the drug-releasing rate [51]. Formulations that can minimize the particle aggregation at nasal pH would be required to ensure the intranasal stability of liposomes, as cationic liposomes are prone to aggregation in physiological conditions [88]. Setting reliable in vitro or ex vivo study models that can test the impact of these formulation factors would be essential for facilitating the development of liposome formulations for nose-to-brain delivery.…”
Section: Conclusion: Implications For Future Developmentmentioning
confidence: 99%
“…in addition, PeG-dMG dissociated rapidly from PeGylated lipid nanoparticle-encapsulated sirna, but PeG-dSG dissociated slowly (11). Furthermore, incorporation of PeG-chol into cationic liposomes was stabilized in human urine and enhanced cellular uptake, whereas the incorporation of PeG-dSPe or PeG-dSG into cationic liposomes effectively prevented the formation of agglomeration but decreased cellular uptake (12). These findings suggested that anchors of PeG derivatives in PeGylated sirna lipoplexes strongly affected cellular association and stability in the blood circulation.…”
Section: Introductionmentioning
confidence: 96%
“…To improve the poor solubility and enhance the efficiency of the cell wall skeleton (CWS) of BCG, Nakamura’s group encapsulated the CWS of BCG within liposomes ( Nakamura et al, 2014 ). Recently, they modified cationic liposomal surfaces with cholesteryl-PEG to overcome urine aggregation and promote cellular uptake into cancerous urothelial tissues ( Nakamura et al, 2017 ). Liposomes can be also used to envelop small interfering RNA (siRNA) silencing oncogenes or other tumor-related genes for the prevention or treatment of BCa.…”
Section: Nanotechnology In Bladder Cancermentioning
confidence: 99%